Chemistry Platform for the Ultrafast Continuous Synthesis of High‐Quality III–V Quantum Dots. Issue 51 (4th August 2021) - Giroire, Baptiste; Garcia, Alain; Marre, Samuel; Cardinal, Thierry; Aymonier, Cyril
Abstract: A chemistry platform for the fast continuous synthesis of III–V quantum dots is demonstrated. III‐nitride QDs are prepared by using short residence times (less than 30 s) in a one‐step continuous process with supercritical solvents. GaN QDs prepared via this route exhibit strong UV photoluminescence with a structuring of the emission signal at low temperature (5 K), confirming their high quality. An example of metal site substitution is given with the synthesis of Inx Ga1‐x N solid solution. A continuous bandgap shift towards lower energies is demonstrated when increasing the indium content with strong photoluminescence signals from UV to visible. The chemistry platform proposed could be easily extrapolated to binary and ternary III phosphides or arsenides with the homologous V source. Abstract : A III–V quantum dots (QDs) chemistry platform is presented. III‐nitrides QDs are prepared in short residence times in a one‐step continuous process involving supercritical solvents. Inx Ga1‐x N QDs fabricated via this platform exhibit strong photoluminescence with continuous bandgap shift towards lower energies measured when increasing indium content. The chemistry platform proposed could be easily transferred to other binary and ternary III–V systems source.